On the attack against aphids - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
CABl's International Institute of Biological Control (IIBC) reports good progress in the search or nature enemies of the three serious forest pests of Malawi's conifer plantations. Natural enemy complexes have been found for all three aphids, the...